Overcoming environmental scarcity, inequality and structural imbalance in the world economy. Issue 3 (3rd July 2019) - Barbier, Edward B.
ABSTRACT: The world economy faces two major threats: increasing environmental degradation and a growing gap between rich and poor. The root cause is that natural resources—or natural capital—is underpriced, and hence overly exploited, whereas human capital—the skills embodied in the workforce—is insufficient to meet demand. This outcome has three important consequences. First, all sectors of an economy will use too much natural resources relative to skilled labor. Second, the skilled workers throughout the economy will have higher real incomes and thus will be better off. Third, wealth inequality will increase, as the income gap between skilled and unskilled workers widens. Addressing this structural imbalance requires correcting the two underlying distortions, which are the chronic under-pricing of natural capital and the under-investment in human capital. This must be accompanied by a new suite of policies to provide improved incentives for more balanced wealth creation.